DISTRIBUTION DATA FOR THE GENUS CLEPTES LATREILLE, 1802 (HYMENOPTERA: CHRYSIDIDAE, CLEPTINAE) OF TURKEY WITH A CHECKLIST OF THE GENUS (Acta Entomologica Serbica, 2020)
The present study is based on samples collected in various locations in Turkey since the 1990s. Together with literature sources, a total of 25 species of the genus Cleptes Latreille, 1802 (Cleptinae) are listed for the country, and C. syriacus Buysson, 1887 is newly recorded for Turkish fauna. A detailed revision of literature data provided new insight into the species composition of this genus in Turkey. Most of the Cleptes species are very rarely collected and are known from one-two provinces: 10 species are known only from one province and five species only from two provinces. Four species are sparsely recorded from different parts of Turkey, whereas only three species, namely C. ignitus, C. scutellaris and C. splendidus, are widely recorded. Currently, seven species are considered endemic, and five are listed as doubtful for the country. A detailed checklist of the genus Cleptes and a distribution map are provided.